2014
DOI: 10.1111/dom.12389
|View full text |Cite
|
Sign up to set email alerts
|

Fat‐free mass loss generated with weight loss in overweight and obese adults: what may we expect?

Abstract: There is concern that intentional weight loss may generate excessive loss of fat-free mass (FFM). Idealists target minimal loss of FFM, while others consider that FFM loss of up to 25% of weight loss is acceptable. In a cross-sectional study of 275 weight-stable, overweight or obese adults, we used whole-body dual-energy X-ray absorptiometry to measure FFM. A range of models was used to estimate the expected ΔFFM/Δweight ratio required to attain the body composition of a weight-stable individual at a lower bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 6 publications
1
19
1
Order By: Relevance
“…(89) The statistically significant decreases in BMD observed in this meta-analysis (-0.010 to -0.015 g/cm 2 ) represent an approximately 1% to 1.5% change from baseline values, which is similar to the average yearly BMD loss for elderly women. (83,90) In an untreated population, each standard deviation decrease in femoral neck BMD (which is 0.12 g/cm 2 ) was associated with an approximately 3.5-fold increase in the risk of hip fracture.…”
Section: Discussionsupporting
confidence: 66%
“…(89) The statistically significant decreases in BMD observed in this meta-analysis (-0.010 to -0.015 g/cm 2 ) represent an approximately 1% to 1.5% change from baseline values, which is similar to the average yearly BMD loss for elderly women. (83,90) In an untreated population, each standard deviation decrease in femoral neck BMD (which is 0.12 g/cm 2 ) was associated with an approximately 3.5-fold increase in the risk of hip fracture.…”
Section: Discussionsupporting
confidence: 66%
“…While the meta-analyses synthesized here show a clear effect of obesity treatments to reduce hip BMD, it is not known whether this is a maladaptive change, or whether it simply represents normalization of BMD relative to reduced body mass, akin to the finding that a certain loss of percent fat-free mass is to be expected in response to reduced BMI [94]. It is also not known whether the observed reductions in hip BMD persist or worsen years after completion of the intervention, as suggested in some [63] but not all [55] of a limited number of studies that assessed bone at > 12 months after bariatric surgery.…”
Section: Expert Opinionmentioning
confidence: 80%
“…There is speculation that bone loss in response to dietinduced weight loss is a normal adaptation to a lighter body [93], akin to the finding that significant reductions in fat free mass are also a normal adaptation to weight loss in adults with overweight or obesity [94]. Furthermore, it has been suggested that while BMD may decline due to diet-induced weight loss, bone quality -as assessed by high resolution magnetic resonance imaging of trabecular bone microarchitecture -does not [95].…”
Section: Effects Of Dietary Restriction On Bonementioning
confidence: 99%
“…A widely cited rule (“Quarter FFM Rule”), guiding expected loss of FFM during weight loss, states that the expected loss of FM will be approximately three fourths of the total weight loss and the remaining one fourth will be loss of FFM [18]. However, this is at best an approximation since the proportion of FFM loss varies over time during weight loss and depends on several factors such as degree of baseline adiposity, gender, level of physical activity, amount of energy intake, and diet composition [1821]. After a 15% reduction in body weight, Kulovitz et al [19] described a 3:1 ratio between FM and FFM loss both in an integrated medical therapy group and post-bariatric surgery.…”
Section: Discussionmentioning
confidence: 99%